Analisis Keputusan Gen Z dalam Menggunakan Qris Sebagai Alat Pembayaran Digital - Ekawati, Farida; Alamsyah, Cik; Wati, Ida (JOURNAL OF INTERDISCIPLINARY SCIENCE AND EDUCATION, 2024)
This study aims to analyze the decision-making process of Generation Z in using QRIS as a digital payment tool. QRIS (Quick Response Code Indonesian Standard) is a standardized payment method based on QR codes developed by Bank Indonesia (BI) and the Indonesian Payment System Association (ASPI). The research adopts a quantitative approach, using a questionnaire distributed to 100 respondents as the sample. Data analysis is conducted using multiple linear regression with the assistance of SPSS software. The results show that, in part, the variables of perceived usefulness, trust, and security risk have a positive and significant impact on Generation Z's decision to use QRIS. Specifically, the greater the perceived benefits and trust in QRIS, the higher the likelihood that Generation Z will choose to use it. However, security risk was found to have a negative effect on the decision to use QRIS. The study concludes that QRIS offers significant convenience and security, but the perceived risks must be managed to enhance adoption by Generation Z.